Comme il Faut: A System for Authoring Playable Social Models - McCoy, Joshua; Treanor, Mike; Samuel, Ben; Wardrip-Fruin, Noah; Mateas, Michael (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2011)
Authoring interactive stories where the player is afforded a wide range of social interactions results in a very large space of possible social and story situations. The amount of effort required to individually author for each of these circumstances can quickly become intractable. The social AI system Comme il Faut (CiF) aims to reduce the burden on the author by providing a playable model of social interaction where the author provides reusable and recombinable representations of social norms and social interactions. Motivated through examples from an in-development video game, Prom Week, this paper provides a detailed description of the structures with which CiF represents social knowledge and how this knowledge is employed to simulate social interactions between characters.